SISTEM KERJA APARATUR SIPIL NEGARA DI KESATUAN BRIGIF MEKANIS SATU PENGAMAN IBU KOTA/JAYA SAKTI SELAMA PANDEMI COVID-19: The Work System of the State Civil Apparatus in the Brigif Mekanis Satu Pengaman Ibu Kota/Jaya Sakti During the COVID-19 Pandemic - Indra Yudha Pratama; Wiratno (Faculty of Law, Universitas Trisakti, 2025)
The COVID-19 pandemic has brought major changes to people's lives, including its impact on the work system. Various policies are implemented as an effort to adjust the work system during the COVID-19 pandemic. In connection with this, this study aims to identify whether the implementation of the latest work system of the State Civil Apparatus (ASN) during the Enforcement of Restrictions on Community Activities (PPKM) in the Brigif Mekanis 1 Safety of the Capital / Jaya Sakti Unit is in accordance with the applicable laws and regulations, and to find out the obstacles faced. This research uses a normative juridical method with a descriptive approach, which is sourced from primary and secondary data, and data collection is carried out through literature study. The results showed that the determination of the latest work system of ASN in the Brigif Mekanis 1 Safety of the Capital / Jaya Sakti Unit during PPKM set a maximum office attendance of 50%. In addition, the obstacles that arise related to the implementation of the new work system during PPKM are not significantly felt.